Methodism and public life in Zimbabwe : an analysis of the Wesleyan Methodist Church in Zimbabwe's impact on politics from 1891-1980 - Duncan, Graham A (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.